2009
DOI: 10.1007/s12031-009-9304-6
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic Actions of Bone Marrow Stromal Cells on Primary Culture of Dorsal Root Ganglion Tissues and Neurons

Abstract: Application of adult bone marrow stromal cells (BMSCs) provides therapeutic benefits to the treatment of neurological insults. The aim of this study was to explore the potential of nonhematopoietic BMSCs to produce soluble factors and stimulate signaling pathways in neurons that mediate trophic effects. A combination of enzyme-linked immunosorbent assay and two-dimensional gel electrophoresis coupled with mass spectrometry showed that the BMSCs released into the culture medium an array of soluble factors such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 47 publications
4
28
0
Order By: Relevance
“…Similar findings were also reported in in vitro [2629] and in vivo [3032] models of spinal cord injury. For instance, Führman et al [28] and Gu et al [29] reported that coculture of BMSCs with dorsal root ganglia (DRG) explants and neurons significantly enhanced neuronal cell survival and neurite outgrowth, through the secretion of NGF, BDNF, bFGF, and CNTF (ciliary neurotrophic factor), HGF, SDF-1 (stromal cell-derived factor 1), VEGF, EGF, NT-3 (neurotrophin-3), and NT-4 (neurotrophin 4) GFs, as well as IL-1 (interleukin-1), IL-6, and IL-8 (interleukin-8) cytokines.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar findings were also reported in in vitro [2629] and in vivo [3032] models of spinal cord injury. For instance, Führman et al [28] and Gu et al [29] reported that coculture of BMSCs with dorsal root ganglia (DRG) explants and neurons significantly enhanced neuronal cell survival and neurite outgrowth, through the secretion of NGF, BDNF, bFGF, and CNTF (ciliary neurotrophic factor), HGF, SDF-1 (stromal cell-derived factor 1), VEGF, EGF, NT-3 (neurotrophin-3), and NT-4 (neurotrophin 4) GFs, as well as IL-1 (interleukin-1), IL-6, and IL-8 (interleukin-8) cytokines.…”
Section: Introductionsupporting
confidence: 87%
“…For instance, Führman et al [28] and Gu et al [29] reported that coculture of BMSCs with dorsal root ganglia (DRG) explants and neurons significantly enhanced neuronal cell survival and neurite outgrowth, through the secretion of NGF, BDNF, bFGF, and CNTF (ciliary neurotrophic factor), HGF, SDF-1 (stromal cell-derived factor 1), VEGF, EGF, NT-3 (neurotrophin-3), and NT-4 (neurotrophin 4) GFs, as well as IL-1 (interleukin-1), IL-6, and IL-8 (interleukin-8) cytokines. This expression pattern is in accordance with data published by others upon BMSCs transplantation in animal models of SCI [3032].…”
Section: Introductionmentioning
confidence: 99%
“…MSCs secretomes present a high range of molecules, such as cytokines and growth factors 11, 3032 . BDNF is a neurotrophin that, together with TrkB, its cognate receptor, is present throughout CNS 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Actually, previous reports have shown that the BMSC produced NGF, BDNF, neurotrophin-3, and glial cell line-derived neurotrophic factor [39]. Furthermore, the BMSC-conditioned medium activates phosphorylation of mitogen-activated protein kinase/extracellular signal-regulated protein kinase and/or phosphoinositide 3-kinase/serine/threonine kinase (Akt) in primary culture of rat dorsal root ganglion neurons [40]. The BMSC markedly promote the neurite extension from the neurons in the organotypic slice of the spinal cord [41].…”
Section: Discussionmentioning
confidence: 99%